(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
The Triassic pterosaur Austriadactylus cristatus is reported for the first time from the Norian (Upper Triassic) of north-eastern Italy. It is only the second specimen of this taxon and provides new information on the mandibular dentition, cranium and postcranium (cervical vertebrae and the forelimb), not available in the holotype. A cladistic analysis shows that Austriadactylus is phylogenetically closer to Preondactylus than to Eudimorphodon.